Salmonella-related mycotic aneurysm: a rare but fatal condition - Sadar, Aarsha; Raj C. N., Arun; R., Legha; R., Jayaprakash (International Journal of Research in Medical Sciences, 2022)
Salmonella species commonly causes gastrointestinal infection in humans. Occasionally they lead to serious complications such as mycotic aneurysms which are rare but potentially fatal. Mortality is high without timely intervention. The clinical presentation is variable and early diagnosis requires a high degree of clinical alertness. Here, we reported a case of mycotic aneurysm secondary to Salmonella enteritidis infection. The case highlights the need to evaluate all elderly patients with non-typhoid Salmonella bacteremia for possible endovascular infections.